2008
DOI: 10.1021/jm800168s
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Aromatase and Dual Aromatase−Steroid Sulfatase Inhibitors from the Letrozole Template: Synthesis, Absolute Configuration, and In Vitro Activity

Abstract: To explore aromatase inhibition and to broaden the structural diversity of dual aromatase-sulfatase inhibitors (DASIs), we introduced the steroid sulfatase (STS) inhibitory pharmacophore to letrozole. Letrozole derivatives were prepared bearing bis-sulfamates or mono-sulfamates with or without adjacent substituents. The most potent of the achiral and racemic aromatase inhibitor was 40 (IC 50 = 3.0 nM). Its phenolic precursor 39 was separated by chiral HPLC, and the absolute configuration of each enantiomer was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 58 publications
3
55
0
Order By: Relevance
“…A chiral HPLC study of the two enantiomers of II following sulfamoylation confirmed that no racemization had taken place during this step. 5 We can thus safely conclude that the sulfamate retains the AC of its corresponding phenol, as confirmed by the observation that the ECD spectra of the two compounds are quite similar. In other cases presented in the literature, the AC of a compound has been assessed by the preparation of a convenient derivative as long as the synthesis of the derivative leaves the stereogenic carbons unchanged (see for example 18 ).…”
supporting
confidence: 58%
See 4 more Smart Citations
“…A chiral HPLC study of the two enantiomers of II following sulfamoylation confirmed that no racemization had taken place during this step. 5 We can thus safely conclude that the sulfamate retains the AC of its corresponding phenol, as confirmed by the observation that the ECD spectra of the two compounds are quite similar. In other cases presented in the literature, the AC of a compound has been assessed by the preparation of a convenient derivative as long as the synthesis of the derivative leaves the stereogenic carbons unchanged (see for example 18 ).…”
supporting
confidence: 58%
“…2) reveals that with the first basis set, already used in Ref. 5, two negative bands are calculated and not observed at 1370 cm 21 and at 1435 cm…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations